Association between risk factors, basal viral load, virus genotype and the degree of liver fibrosis with the response to the therapy in patients with chronic hepatitis C virus infection - Vuković, Vuk R.; Baskić, Dejan; Mijailović, Željko; Djurdjević, Predrag; Jovanović, Danijela; Mitrović, Slobodanka; Popović, Suzana (Vojnosanitetski pregled, 2015)
Background/Aim. Hepatitis C is an important sociomedical problem worldwide due to frequent progression to chronic disease, occurrence of liver cirrhosis and hepatocellular carcinoma. Standard pegylated interferon alfa 2a plus ribavirin therapy results in resolution of infection only in 50% of patients. The aim of this study was to determine the association of various factors with response to the therapy in patients with chronic heptitis C virus (HCV) infection. Age and sex of patients, inoculation risk factors, histopathological changes in the liver, viral load and HCV genotype were analyzed. Methods. The study included a group of 121 patients with chronic HCV infection. The treatment was carried out 24 weeks for virus genotype 2 and 3, and 48 weeks for genotype 1 and 4. The degree of histopathological changes in the liver was determined by hematoxylin and eosin staining, whereas polimerase chain reaction was used for HCV genotyping. Results. In the group of non-responding patients genotype 1 was represented with 100%, while in the other groups, although predominantly present, its percentage was lower. Unresponsiveness to therapy and relapse of disease were associated with higher viral load and advanced fibrosis. Intravenous use of psychoactive substances, as a risk factor, was present in a high percentage in the group of patients with sustained response, while blood transfusion and dialysis were leading risk factors in the group of relapse responders and non-responders. Conclusion. The results of our study showed that the treatment outcome of chronic HCV infection was associated with baseline HCV ribonucleic acid, HCV genotype, route of infection and the degree of histopathological changes in the liver.